2015
DOI: 10.1111/dote.12337
|View full text |Cite
|
Sign up to set email alerts
|

Early enteral nutrition compared with parenteral nutrition for esophageal cancer patients after esophagectomy: a meta-analysis

Abstract: Early postoperative enteral nutrition (EN) after esophagectomy in esophageal cancer patient has been reported to be correlated with a better rehabilitation than parenteral nutrition (PN). However, a robust conclusion has not been achieved. Therefore, we performed a meta-analysis to compare the postoperative EN and PN in patients with esophageal cancer undergoing esophagectomy. Three electronic databases were searched for eligible studies to be included in the meta-analysis. The summary relative risk/weighted m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
33
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 24 publications
3
33
0
2
Order By: Relevance
“…No difference was observed in digestive complications between these two approaches. However, this meta-analysis is characterized by heterogeneity issues, especially regarding the postoperative nutritional status [70]. Furthermore, others suggest that combination of enteral and parenteral feeding is more beneficial, since total parenteral nutrition (TPN) could lead to hyperglycemia in stressed patients.…”
Section: Enteral Versus Parenteral Nutritionmentioning
confidence: 99%
“…No difference was observed in digestive complications between these two approaches. However, this meta-analysis is characterized by heterogeneity issues, especially regarding the postoperative nutritional status [70]. Furthermore, others suggest that combination of enteral and parenteral feeding is more beneficial, since total parenteral nutrition (TPN) could lead to hyperglycemia in stressed patients.…”
Section: Enteral Versus Parenteral Nutritionmentioning
confidence: 99%
“…However, in this study, we could not find any association between preservation of the bronchial arteries and postoperative complications. Regarding perioperative management, preoperative respiratory rehabilitation [22], oral care [23], smoking cessation [24], early enteral nutrition after surgery [25], and use of corticosteroids [26] or sivelestat sodium hydrate [27,28] are possible ways to prevent postoperative complications. Cox proportional-hazards models were used for the univariate and multivariate analyses of overall survival in the 73 patients who underwent salvage esophagectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Table 3 summarises studies on EN after oesophagectomy. 3,[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] Although the use of EN is not without its disadvantages, the benefits outweigh the risks. Early EN was compared with delayed nutrition by Wang et al, and was found to be associated with a short LOS, fewer incidences of pneumonia and better nutrition outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…3 Early EN has been found to decrease the length of hospital stay (LOS) and lead to a better outcome than parenteral nutrition (PN), in addition to reducing the total cost of patient care. 4,5 Early EN following oesophagectomy is usually maintained via a nasojejunal tube (NJT), a jejunostomy tube (JT) or a pharyngostomy tube (PT). The use of a NJT for EN after oesophagectomy was first reported by Page et al; however, this method was compared only with PN.…”
mentioning
confidence: 99%